Between Myth and Revolution: Magic Realism in Kiran Manandhar’s Socio-Political Art - Paudel , Sushil; Lamichhane, Dipak; Paudel, Shankar (Journal of Kathmandu BernHardt College, 2025)
This research studies the issue of Magic Realism in the selected paintings of Kiran Manandhar in connection with the democratic revolution in Nepal. Through a series of political and apolitical paintings, Kiran Manandhar explores the relationship between violence and peace. Kiran’s political paintings stand on behalf of people’s rights and question any kind of corrupt, crooked, and autocratic forms of government. He uses inner psyche and his magical forms like vibrant brush strokes, bold colors, dynamic lines, and distorted shapes to express the pain of human suffering under oppressive regimes. The spontaneous and fluid application of colors, the interplay of pencil and brush sketches, and the merging of defined figures with abstract patches create a playful visual art. Though not entirely realistic, his work produces a powerful articulation of political and emotional themes. This research contributes significantly to critical discourse and academic study by examining how Manandhar employs Magic Realism as a political tool in his art. The study serves as a foundation for further exploration of the connections between artistic expression and socio-political movements in Nepal.